Validation of educational games adapted to the national curricular design, for initial and primary levels, of urban and rural areas of Lima, Arequipa and Iquitos - Adrianzen, Silvia (2017)
The research aimed to validate educational games that foster and develop skills related to reading comprehension. That is why an experimental program was carried out, which consisted of the design, development and manufacture of the 13 contextualized educational games, as well as their application in the classroom. The sample was 789 boys and girls of initial 5 years, first and second grade of primary education, belonging to public and private schools, rural and urban areas, of three regions of Peru: Lima, Arequipa and Iquitos. The results of the final evaluation indicated that, after using the educational games in the classroom, scores in reading comprehension and associated skills increased by 15.83%, exceeding the percentage of 10% set as the initial goal. This demonstrates the effectiveness of the use of educational games to significantly improve reading comprehension in children, achieved through the empowerment of playful methodology in teachers, which was a primary factor in achieving these results.